2009
DOI: 10.17305/bjbms.2009.2836
|View full text |Cite
|
Sign up to set email alerts
|

Micophenolat Mofetil Versus Azathioprine: Effects on Renal Graft Function in Early Posttransplant Period

Abstract: All conventional immunosuppressive tree drugs-protocols are based on Cyclosporine; consisting of low doses of Cyclosporine (CsA), Azathioprine (AZA) or Mycophenolate Mofetil (MMF) and Prednisolone. AZA has been used in clinical transplantation for more than  years and was the fi rst immunosuppressive agent to achieve widespread use in organ transplantation. MMF was introduced in clinical practice in  after several clinical trials proved that it was more effi cient than AZA for prevention of acute rejecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…In a study by El-Ashmawy and Bayad, AZAinduced renal damage and its amelioration by treatment with folic acid and grape seed extract were reported for experimental animal model (21). Also, significant higher serum creatinine, lower glomerular filtration rate, and creatinine clearance have been previously found in human subjects and rats treated with AZA (21,25,26). Our study finding revealed that the nephrotoxicity of AZA could have been due to generation of ROS with consequent adverse effects on the functions of the kidney, which was consistence with the results from previous studies reporting the involvement of oxidative stress and lipid peroxidation in AZA-induced liver toxicity.…”
Section: Discussionmentioning
confidence: 96%
“…In a study by El-Ashmawy and Bayad, AZAinduced renal damage and its amelioration by treatment with folic acid and grape seed extract were reported for experimental animal model (21). Also, significant higher serum creatinine, lower glomerular filtration rate, and creatinine clearance have been previously found in human subjects and rats treated with AZA (21,25,26). Our study finding revealed that the nephrotoxicity of AZA could have been due to generation of ROS with consequent adverse effects on the functions of the kidney, which was consistence with the results from previous studies reporting the involvement of oxidative stress and lipid peroxidation in AZA-induced liver toxicity.…”
Section: Discussionmentioning
confidence: 96%
“…Antiproliferative immunosuppressants mainly include mizoribine (MZR), azathioprine (AZA), and mycophenolate mofetil (MMF). AZA is rarely used in recipients after renal transplantation because of its severe hepatotoxicity and bone marrow suppression toxicity [7]. MMF is currently recommended as the first-line drug of antiproliferative drugs, but the application of MMF after renal transplantation is easy to cause gastrointestinal reactions such as diarrhea, abdominal pain, leucopenia, infection, and liver function damage.…”
Section: Introductionmentioning
confidence: 99%